Case Report: The First Record of zoonotic Enterococcus gallinarum in She Camel feces (Camelus dromedaries) - Kadhim, Taisir Abdulelah; Alsafar, Ali Husein Ali; Alabadi, Iman K. M. (American Journal of Biomedicine and Pharmacy, 2025)
Enterococcus gallinarum is a well-known normal flora in the human and animal digestive systems. It is an opportunistic microorganism that increased recently due to the massive use of antibiotics. This study aimed to describe the four years she-camel presented to Al-Muthanna Veterinary Hospital suffering from severe watery diarrhea mixed with blood and pus, dehydration, and anorexia. Other clinical signs were dyspnea and icterus mucous membranes. A fecal swab was collected from rectum in a sterile swab and sent to the laboratory for microbiological investigation and bacterial antibiotic sensitivity test. Fecal swabs were culture in selective medium for bacterial isolation. The isolated strain was identified in AL Hussein Teaching Hospital in Samawah using VITEK® system for fast, accurate, microbial identification and antibiotic susceptibility testing and also routine traditional biochemical tests. According to VITEK® system and biochemical test, E. gallinarum was isolated as pure culture from fecal swab. The isolated microorganism was sensitive for Levofloxacin= 0.25, Erythromycin <= 0.25, Linezolid] 2, Teicoplanin < =0.5, Tigecycline <= 0.12, Fostomycin = 32, while it was resistant to Vancomycin= 2, tetracycline >=16. For our knowledge this is the first report that isolated E. gallinarum from diarrheic she-camel. The intestinal bacterial disease showed diarrhea that was accompanied with massive portions of inflammatory exudate which contains blood, pus, and proteinaceous material. Precautionary measures need to be taken to avoid the severe draw back consequences of E. gallinarum infection.